Kajian Antioksidan, Total Fenol & Total Flavonoid Jamu Selokarang yang diformulasi dengan Jinten Hitam (Nigella sativa) - Sukardi Sukardi; Noer Iqbal Arief Iqbal; Sri Winarsih (Food Technology and Halal Science Journal, 2021)
Abstrcact Jamu Selokarang is one of the traditional drinks originating from an area, namely Madura, the ingredients used in the manufacture of Jamu Selokarang are turmeric, ginger, ginger, betel leaf, soursop leaves, cloves, nutmeg, coriander, temu ireng and ginger. The ingredients used in the manufacture of herbal medicine selokarang contain a lot of antioxidants and essential oils. Testing is needed to determine the antioxidant activity contained in the herbal medicine selokarang. This study aims to determine the effect of substitution of jamu selokarang on antioxidant compounds, total phenols, flavonoids, ash content and water content. This study used a simple completely randomized design method (simple CRD) with a single factor, namely the black cumin formulation of 0%, 2%, 4%, 6% and 8% which were included in jamu selokarang. The research was repeated 3 times. The parameters observed were: water content, ash content, antioxidants, total phenols, and flavonoids. The results showed that the substitution had a significant effect on water content, ash content and antioxidant activity, while the total phenol and flavonoid analysis had no significant effect. Treatment 0% black cumin had water content of 2.68%; Ash content of 7,90%; DPPH anti-oxidant for 49.08%; antioxidant FRAP 26.25 μgAAE / mL; total phenol was 2.05 μgGAE / mg, and total flavonoids was 0.91 μgQAE / mg.